Effect of organic amendments on Aloe vera growth in nursery in Daloa, Côte d’Ivoire - Désiré, N’goran Koffi; Charlotte, Tonessia Dolou; Francis, Soumahin Eric; Dominique, Zoh Olivia; Junias, Sey; Selastique, Akaffou Doffou (International Journal of Environment, Agriculture and Biotechnology, 2023)
In the face of climate change, the optimization of crop diversification policy in Côte d'Ivoire must go through research and promotion of crops of interest that require little water, including Aloe vera. However, in view of its slow growth in nursery, the improvement of growth substrate fertility by the supply of nutrients is necessary. Thus, this study aims at assessing the effects of six organic matter formulations on Aloe vera growth in nursery. To this end, a completely randomized block experimental design comprising six treatments and three replications was carried out. The amendments tested were cow dung, chicken droppings, charcoal, banana tree stems and ripe plantain and dessert bananas. The results showed substrate pH variability (6.67 to 7.87) depending on the amendments. Leaf emergence speed increased with cow dung from the 80th day after planting. Similarly, the highest number of leaves was obtained with cow dung (9.33 leaves). With 22.89 cm in average length and 1.65 cm in average width, the leaves generated with cow dung were also the longest and widest. This study showed that cow dung promotes rapid Aloe vera growth in nursery.